Rhetoric in Video Uploads by the Detective Doctor Account on TikTok and Its Implications for Indonesian Language Learning in Vocational Schools - Radita Isnalela, Nada; Muljani, Sutji; Anwar, Syamsul (Bahasa Indonesia Prima, 2025)
This research is motivated by social media such as TikTok in the dissemination of information owned by Dokter Detektif to reveal health cases using rhetorical techniques to improve students speaking skills. This study aims to describe the rhetorical techniques used in the video uploads of the Dokter Detektif account on TikTok social media and describe the implications of the research results for Indonesian language learning in vocational schools. This study uses a qualitative descriptive method. The data collection technique uses the listening method with the technique of free listening and speaking, note-taking, and documentation. The results show that in the video uploads of the Dokter Detektif account on TikTok social media, 54 rhetorical utterances consisting of ethos, pathos, and logos. Of the three logos appears most dominant, followed by pathos, and then ethos. The dominant of logos that the information conveyed in the video relies more on logic and facts to convince the audience. The results of the study have implications for Indonesian language learning in SMK Phase E on the Negotiation text material which can train speaking skills.